Encontrar el valor solicitado
1
Encuentra el valor de x del siguiente sistema: Ec(1): [ 2x + 3y = - 30 ], Ec(2): [ 3x + 7y = - 60 ]
2
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 9x + 3y = 57 ], Ec(2): [ - 9x - 5y = 1 ]
3
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 2x + 9y = - 15 ], Ec(2): [ 5x + 4y = 11 ]
4
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 7x - 6y = 30 ], Ec(2): [ 6x + 3y = - 30 ]
5
Encuentra el valor de x del siguiente sistema: Ec(1): [ 8x + 4y = 44 ], Ec(2): [ 9x + 7y = 42 ]
6
Encuentra el valor de x del siguiente sistema: Ec(1): [ 5x - 3y = 42 ], Ec(2): [ - 9x - 3y = - 84 ]
7
Encuentra el valor de x del siguiente sistema: Ec(1): [ 6x + 4y = - 68 ], Ec(2): [ - 4x - 7y = 67 ]
8
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 6x - y = - 29 ], Ec(2): [ - 3x + 8y = - 23 ]
9
Encuentra el valor de x del siguiente sistema: Ec(1): [ 8x - 2y = 56 ], Ec(2): [ 7x - y = 52 ]
10
Encuentra el valor de x del siguiente sistema: Ec(1): [ 4x - 2y = 14 ], Ec(2): [ - 4x - 4y = - 68 ]
11
Encuentra el valor de x del siguiente sistema: Ec(1): [ x - 5y = - 48 ], Ec(2): [ - 8x - 9y = - 8 ]
12
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 7x - 5y = 23 ], Ec(2): [ 8x + 7y = - 16 ]
13
Encuentra el valor de x del siguiente sistema: Ec(1): [ x - y = - 10 ], Ec(2): [ - 4x + 5y = 41 ]
14
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 3x + 9y = 39 ], Ec(2): [ - 5x + 9y = 47 ]
15
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 5x - 2y = - 3 ], Ec(2): [ 9x - 5y = 57 ]
16
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 5x - 2y = - 3 ], Ec(2): [ 9x - 5y = 57 ]
17
Encuentra el valor de x del siguiente sistema: Ec(1): [ 8x + 2y = - 2 ], Ec(2): [ - 4x - 5y = 37 ]
18
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 8x + 7y = - 19 ], Ec(2): [ - x - 8y = - 29 ]
19
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 7x + 7y = 0 ], Ec(2): [ - 5x - 3y = 64 ]
20
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 8x + 2y = 44 ], Ec(2): [ - 5x + 9y = - 19 ]
21
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 6x + 4y = - 40 ], Ec(2): [ 2x - 6y = 4 ]
22
Encuentra el valor de y del siguiente sistema: Ec(1): [ 3x - 3y = 9 ], Ec(2): [ - 2x - 7y = 3 ]
23
Encuentra el valor de y del siguiente sistema: Ec(1): [ 2x - 3y = - 37 ], Ec(2): [ 6x - 6y = - 84 ]
24
Encuentra el valor de y del siguiente sistema: Ec(1): [ 2x - y = 4 ], Ec(2): [ - 5x - 7y = 66 ]
25
Encuentra el valor de y del siguiente sistema: Ec(1): [ - 7x - 8y = - 1 ], Ec(2): [ - 6x + 2y = 8 ]
26
Encuentra el valor de y del siguiente sistema: Ec(1): [ - 4x + 6y = 36 ], Ec(2): [ - 2x - 5y = - 14 ]
27
Encuentra el valor de y del siguiente sistema: Ec(1): [ 6x - 6y = - 96 ], Ec(2): [ - x - 2y = - 8 ]
28
Encuentra el valor de y del siguiente sistema: Ec(1): [ 4x + 4y = 40 ], Ec(2): [ 8x - 5y = 67 ]
29
Encuentra el valor de y del siguiente sistema: Ec(1): [ 6x - y = 31 ], Ec(2): [ 9x + 3y = 15 ]
30
Encuentra el valor de y del siguiente sistema: Ec(1): [ - 5x - 7y = 46 ], Ec(2): [ 4x - 2y = 24 ]
31
Encuentra el valor de y del siguiente sistema: Ec(1): [ - 4x - 7y = 27 ], Ec(2): [ 4x + y = - 21 ]
32
Encuentra el valor de y del siguiente sistema: Ec(1): [ - x + 6y = - 27 ], Ec(2): [ x + 5y = - 39 ]
33
Encuentra el valor de y del siguiente sistema: Ec(1): [ 9x - 2y = 79 ], Ec(2): [ 4x - 7y = 29 ]
34
Encuentra el valor de y del siguiente sistema: Ec(1): [ - 5x - 8y = 28 ], Ec(2): [ 8x - 5y = 62 ]
35
Encuentra el valor de y del siguiente sistema: Ec(1): [ - x + 6y = 41 ], Ec(2): [ 5x + 9y = 29 ]
36
Encuentra el valor de y del siguiente sistema: Ec(1): [ 8x + 9y = 9 ], Ec(2): [ x + 5y = 36 ]
37
Encuentra el valor de y del siguiente sistema: Ec(1): [ - 8x + 6y = - 80 ], Ec(2): [ - 2x + 6y = - 38 ]
38
Encuentra el valor de y del siguiente sistema: Ec(1): [ - 5x - 2y = - 9 ], Ec(2): [ 3x - 8y = 79 ]
39
Encuentra el valor de y del siguiente sistema: Ec(1): [ - 8x + 3y = - 5 ], Ec(2): [ - 7x - 5y = 49 ]
40
Encuentra el valor de y del siguiente sistema: Ec(1): [ - 6x + y = - 29 ], Ec(2): [ 4x + 2y = 6 ]
41
Encuentra el valor de y del siguiente sistema: Ec(1): [ - 4x - 4y = 40 ], Ec(2): [ - 8x + 6y = - 32 ]
42
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 8x - 8y = - 8 ], Ec(2): [ - 4x - 9y = 21 ]
43
Encuentra el valor de x del siguiente sistema: Ec(1): [ 9x - 3y = - 18 ], Ec(2): [ 8x - 4y = - 4 ]
44
Encuentra el valor de x del siguiente sistema: Ec(1): [ 9x - 3y = - 9 ], Ec(2): [ 5x - 3y = - 17 ]
45
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 4x + 6y = - 4 ], Ec(2): [ - 9x - 8y = 120 ]
46
Encuentra el valor de x del siguiente sistema: Ec(1): [ 3x + 7y = 54 ], Ec(2): [ 9x + 9y = 54 ]
47
Encuentra el valor de x del siguiente sistema: Ec(1): [ 7x + 9y = 16 ], Ec(2): [ - 2x - 7y = - 40 ]
48
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 5x + 2y = - 46 ], Ec(2): [ - 4x + 5y = - 64 ]
49
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 3x - 6y = 36 ], Ec(2): [ 5x + 3y = - 39 ]
50
Encuentra el valor de x del siguiente sistema: Ec(1): [ 7x + 2y = 2 ], Ec(2): [ 4x + 4y = - 16 ]
51
Encuentra el valor de x del siguiente sistema: Ec(1): [ 3x - 5y = 17 ], Ec(2): [ - 4x - 8y = - 8 ]
52
Encuentra el valor de y del siguiente sistema: Ec(1): [ - 7x + 2y = 29 ], Ec(2): [ 9x + 6y = - 3 ]
53
Encuentra el valor de y del siguiente sistema: Ec(1): [ 6x + 6y = 36 ], Ec(2): [ 3x + 5y = 12 ]
54
Encuentra el valor de y del siguiente sistema: Ec(1): [ - 4x - 7y = 68 ], Ec(2): [ 3x - 4y = 23 ]
55
Encuentra el valor de y del siguiente sistema: Ec(1): [ 7x + 3y = - 39 ], Ec(2): [ 4x + y = - 18 ]
56
Encuentra el valor de y del siguiente sistema: Ec(1): [ 4x - 4y = 20 ], Ec(2): [ 5x + 5y = - 45 ]
57
Encuentra el valor de y del siguiente sistema: Ec(1): [ - 2x - 5y = - 12 ], Ec(2): [ 7x - 4y = - 44 ]
58
Encuentra el valor de y del siguiente sistema: Ec(1): [ - 5x - 7y = 31 ], Ec(2): [ - 9x + 6y = 0 ]
59
Encuentra el valor de y del siguiente sistema: Ec(1): [ - 4x + 5y = - 23 ], Ec(2): [ - 3x + 4y = - 19 ]
60
Encuentra el valor de y del siguiente sistema: Ec(1): [ 9x + 3y = - 51 ], Ec(2): [ 2x - 9y = 8 ]
61
Encuentra el valor de y del siguiente sistema: Ec(1): [ x - 9y = 67 ], Ec(2): [ 6x - 6y = 66 ]
62
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 7x + 5y = - 73 ], Ec(2): [ - x + 4y = - 17 ]
63
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 8x - 5y = 11 ], Ec(2): [ x - 3y = - 34 ]
64
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 3x - 3y = 15 ], Ec(2): [ 8x - 8y = 104 ]
65
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 2x - 4y = - 34 ], Ec(2): [ x - 9y = - 38 ]
66
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 8x - 4y = 76 ], Ec(2): [ 9x - 8y = - 73 ]
67
Encuentra el valor de y del siguiente sistema: Ec(1): [ - 7x - 9y = - 82 ], Ec(2): [ 7x - 7y = - 14 ]
68
Encuentra el valor de y del siguiente sistema: Ec(1): [ 9x + 9y = - 45 ], Ec(2): [ 6x - y = 12 ]
69
Encuentra el valor de y del siguiente sistema: Ec(1): [ 7x + y = - 22 ], Ec(2): [ - 2x + 7y = - 52 ]
70
Encuentra el valor de y del siguiente sistema: Ec(1): [ 7x - 6y = - 41 ], Ec(2): [ 3x + 8y = - 7 ]
71
Encuentra el valor de y del siguiente sistema: Ec(1): [ 6x + 7y = 39 ], Ec(2): [ - x - 8y = - 68 ]
72
Encuentra el valor de x del siguiente sistema: Ec(1): [ 9x - 8y = 22 ], Ec(2): [ 8x + y = 52 ]
73
Encuentra el valor de x del siguiente sistema: Ec(1): [ 6x + y = 25 ], Ec(2): [ x + 5y = 9 ]
74
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 4x - 2y = 10 ], Ec(2): [ - 4x + 6y = - 14 ]
75
Encuentra el valor de x del siguiente sistema: Ec(1): [ 7x - y = 2 ], Ec(2): [ 2x + 3y = - 29 ]
76
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 4x - 2y = 2 ], Ec(2): [ x + y = 3 ]
77
Encuentra el valor de y del siguiente sistema: Ec(1): [ 9x - 3y = - 27 ], Ec(2): [ - 3x - 3y = 33 ]
78
Encuentra el valor de y del siguiente sistema: Ec(1): [ 3x + 9y = 18 ], Ec(2): [ - 5x - 5y = 20 ]
79
Encuentra el valor de y del siguiente sistema: Ec(1): [ 7x + 4y = 39 ], Ec(2): [ - 7x - 3y = - 45 ]
80
Encuentra el valor de y del siguiente sistema: Ec(1): [ 4x - 6y = - 2 ], Ec(2): [ 4x - 2y = - 22 ]
81
Encuentra el valor de y del siguiente sistema: Ec(1): [ - 5x - 6y = 51 ], Ec(2): [ 7x - 7y = 21 ]
82
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 2x + y = 1 ], Ec(2): [ - 7x - 9y = - 59 ]
83
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 8x - 9y = 6 ], Ec(2): [ - x - y = 1 ]
84
Encuentra el valor de x del siguiente sistema: Ec(1): [ 3x + 5y = - 8 ], Ec(2): [ 8x + 4y = 44 ]
85
Encuentra el valor de x del siguiente sistema: Ec(1): [ 8x - y = 19 ], Ec(2): [ - 8x - 4y = - 4 ]
86
Encuentra el valor de x del siguiente sistema: Ec(1): [ 4x - 5y = 47 ], Ec(2): [ 9x - 8y = 83 ]
87
Encuentra el valor de y del siguiente sistema: Ec(1): [ 7x + 9y = 60 ], Ec(2): [ - 6x + 6y = 72 ]
88
Encuentra el valor de y del siguiente sistema: Ec(1): [ - 6x - 5y = - 1 ], Ec(2): [ - x - y = - 1 ]
89
Encuentra el valor de y del siguiente sistema: Ec(1): [ 4x - 8y = - 40 ], Ec(2): [ - 4x + 3y = 10 ]
90
Encuentra el valor de y del siguiente sistema: Ec(1): [ 2x - 2y = 12 ], Ec(2): [ 4x + 4y = 16 ]
91
Encuentra el valor de y del siguiente sistema: Ec(1): [ 7x - 4y = 6 ], Ec(2): [ 7x + 9y = 123 ]
92
Encuentra el valor de y del siguiente sistema: Ec(1): [ 7x + y = 5 ], Ec(2): [ 2x + 3y = - 23 ]
93
Encuentra el valor de y del siguiente sistema: Ec(1): [ 3x - 3y = 18 ], Ec(2): [ - 6x - 2y = - 12 ]
94
Encuentra el valor de y del siguiente sistema: Ec(1): [ - 9x + 8y = 66 ], Ec(2): [ 2x - 2y = - 16 ]
95
Encuentra el valor de y del siguiente sistema: Ec(1): [ - 7x - 9y = 4 ], Ec(2): [ 6x - 3y = 18 ]
96
Encuentra el valor de y del siguiente sistema: Ec(1): [ - 6x - 9y = - 57 ], Ec(2): [ 6x + 7y = 39 ]
97
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 4x - 3y = 14 ], Ec(2): [ 7x - 4y = - 43 ]
98
Encuentra el valor de x del siguiente sistema: Ec(1): [ 4x - 8y = - 88 ], Ec(2): [ - 4x + 9y = 97 ]
99
Encuentra el valor de x del siguiente sistema: Ec(1): [ - 4x + 2y = - 48 ], Ec(2): [ x - 9y = 63 ]
100
Encuentra el valor de x del siguiente sistema: Ec(1): [ 4x + 4y = 40 ], Ec(2): [ 2x + y = 12 ]
|